Probabilistic Shape Parsing and Action Recognition Through Binary Spatio-Temporal Feature Description - Whiten, Christopher J. (2013)
In this thesis, contributions are presented in the areas of shape parsing for view-based object recognition and spatio-temporal feature description for action recognition. A probabilistic model for parsing shapes into several distinguishable parts for accurate shape recognition is presented. This approach is based on robust geometric features that permit high recognition accuracy.